2020
DOI: 10.1111/acem.14054
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Department–initiated Interventions for Patients With Opioid Use Disorder: A Systematic Review

Abstract: Objectives: The opioid crisis has risen dramatically in North America in the new millennium, due to both illegal and prescription opioid use. While emergency departments (EDs) represent a potentially strategic setting for interventions to reduce harm from opioid use disorder (OUD), the absence of a recent synthesis of literature limits implementation and scalability. To fill this gap, we conducted a systematic review of the literature on interventions targeting OUDs initiated in EDs. Methods: Using an explicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 30 publications
1
25
0
Order By: Relevance
“…12 A systematic review of ED-initiated interventions for patients with OUD found that OAT initiation, including BUP, was the most promising ED intervention; however, further research and efforts to reduce implementation barriers were recommended. 16…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 A systematic review of ED-initiated interventions for patients with OUD found that OAT initiation, including BUP, was the most promising ED intervention; however, further research and efforts to reduce implementation barriers were recommended. 16…”
Section: Introductionmentioning
confidence: 99%
“…Because you know, these are patients with a history of overdose, history of criminality, history of diversion, you know they're not stable patients who you can give a prescription to and expect them to use it in any kind of responsible way." (participant16) Study participants thought that interphysician variability in motivation and ability to initiate BUP in the ED could be minimized by providing basic OAT training via accredited programs tailored specifically for emergency physicians. One participant explained: "I wish there was something that was perhaps a little bit shorter, or 1 specifically geared to emergency physicians.. .…”
mentioning
confidence: 99%
“…Evidence strongly supports the initiation of pharmacotherapy for patients with untreated opioid use disorder at any and all points of contact with the health care system; this has been advocated by the Surgeon General, the National Institute on Drug Abuse, the Substance Abuse and Mental Health Services Administration (SAMHSA), the National Academy of Sciences, and the American College of Emergency Physicians (ACEP). [24][25][26][27][28][29] The ED is often the only contact individuals with opioid use disorder have with the health care system, and initiating treatment during the visit can make an enormous contribution to improving access to lifesaving care for people with opioid use disorder.…”
Section: The Opioid Crisis and Emergency Departmentsmentioning
confidence: 99%
“…23 Patients enrolled in treatment programs that included MOUD without behavioral health interventions and who were enrolled from the ED following a non-fatal overdose were less likely to be enrolled 30 days after initiation. 24,25 Individuals with co-occurring OUD and mental illness are more likely to continue using nonprescription opioids, 26 have increased risk of chronic and acute physical illness, 27 and are at increased risk of accidental 28 and intentional overdose, 29,30 thereby increasing opioid-related mortality. 31 A bulk of research on adults with co-occurring OUD and mental health over the past decade is largely based on national epidemiological surveys, 19,[32][33][34][35][36] retrospective data analysis, 2,[37][38][39] or surveys of individuals in treatment.…”
Section: Prevalence Of Mental Health Disorders Among Individuals Enromentioning
confidence: 99%
“…51,52 Individuals with mental health emergencies in the ED are triaged, stabilized, and released with a referral to community-based mental health services; 49,50,53 and this treat-andrefer model has largely continued with SUD emergencies. 49 Although ED-initiated MOUD is a promising approach to addressing the opioid crisis, 24,25 without prompt follow up with psychosocial services many patients fall through the cracks. 49 Previous research has reported the incidence of co-occurring serious mental illness among individuals with OUD to be anywhere from 26.9% 32 and the co-occurrence of any mental illness as high as 75.6%.…”
Section: Prevalence Of Mental Health Disorders Among Individuals Enrolled In An Emergency Response Program For Treatment Of Opioid Use DImentioning
confidence: 99%